2020
DOI: 10.1080/14756366.2020.1751150
|View full text |Cite
|
Sign up to set email alerts
|

A study of Rose Bengal against a 2-keto-3-deoxy-d-manno-octulosonate cytidylyltransferase as an antibiotic candidate

Abstract: Frequent occurrences of multi-drug resistance of pathogenic Gram-negative bacteria threaten human beings. The CMP-2-keto-3-deoxy- d - manno -octulosonic acid biosynthesis pathway is one of the new targets for antibiotic design. 2-Keto-3-deoxy- d - manno -octulosonate cytidylyltransferase (KdsB) is the key enzyme in this pathway. KdsB proteins from Burkholderia pseudomallei ( Bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Bengal against KDO. [18] The double reciprocal plots confirmed that BpHldC and BpKdsB are allosteric enzymes (Figures S3 and S4).…”
Section: P Aeruginosa Displaying a Competitive Inhibitory Fashion Of Rosesupporting
confidence: 59%
See 3 more Smart Citations
“…Bengal against KDO. [18] The double reciprocal plots confirmed that BpHldC and BpKdsB are allosteric enzymes (Figures S3 and S4).…”
Section: P Aeruginosa Displaying a Competitive Inhibitory Fashion Of Rosesupporting
confidence: 59%
“…A malachite green assay, the photometric method, was carried out for the screening of chemical compounds (Table S1). [18] The reaction mechanism of the three enzymes is similar, except for their substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, affinity chromatography was done and ion-exchange chromatography has followed as the secondary purifications. KdsB proteins from B. pseudomallei , C. jejuni , Chlamydia psittaci , E. coli , Klebsiella aerogenes , N. meningitidis , Pseudomonas aeruginosa , Salmonella enterica , and Vibrio cholerae have been purified according to the previous method 17 . Purification was also carried out with the same process.…”
Section: Methodsmentioning
confidence: 99%